Developing Analytical Thinking Skills with the STAD Collaborative Learning Model for Vocational Certificate Students, Accounting Department Prachinburi Vocational College - Janthar, Narumon (Wisdom Journal of Humanities and Social Sciences, 2024)
The research has an objective. To develop analytical thinking skills With the collaborative learning management model, STAD technique, to develop STAD collaborative teaching methods of teachers and to compare analytical thinking skills between before class and after class of students at vocational certificate level (Vocational Certificate level. Accounting Academic Department Prachinburi Vocational College, 15 people, time spent on research In the first semester of the academic year 2023, between 15 May 2023 - 15 September 2023, 3 learning plans were used in the research. Scores were collected for each plan, 10 points each, and there were 30 pre- and post-test scores. 30 points. After implementing the collaborative teaching method STAD, students' post-test scores showed a significant increase compared to their pre-class scores, meeting 100 percent of the evaluation criteria. The post-test mean score was 27.40 with a standard deviation of 1.30, marking a statistically significant improvement. Students' developmental scores indicated an average of 21.87 and a relative improvement score average of 89.24, reflecting substantial progress. The efficiency value of the learning management plan E1/E2 stood at 92.44/91.33, indicating its high suitability for educational purposes.